Implementation of a Three Phase Motor Protection System Using PLC and HMI - Prasetyo, Yuli; Triyono, Budi; Kusumo H, R. Jasa; Triwijaya, Santi (International Journal of Multidisciplinary Approach Research and Science, 2024)
Three-phase electric motors are essential components in industrial production processes, playing a crucial role as the driving force for almost all industrial machinery. These motors are susceptible to various electrical disturbances, such as overcurrent caused by overloads or short circuits. Common issues that frequently occur with three-phase motors include high starting currents, overcurrent, and short circuits. To mitigate the losses caused by these disturbances, an effective protection system is necessary. This study analyzes the implementation of a protection system using Programmable Logic Controller (PLC) and Human Machine Interface (HMI) to control and monitor the protection mechanisms for electric motors. The proposed protection system aims to safeguard the motors from disturbances such as high starting currents, overcurrent, and short circuits. By leveraging the real-time monitoring and control capabilities of PLCs and the user-friendly interface of HMIs, the system can accurately detect and respond to abnormal conditions, thereby minimizing the risk of damage to critical three-phase motors. The development of this protection system ensures the reliability and longevity of three-phase motors in industrial applications, reducing downtime and enhancing overall operational efficiency.